Nitrogen-doped porous carbon nanorods, and preparation method and application thereof

CN117756098BActive Publication Date: 2026-10-27TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311851737.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2026-10-27
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

但同样地,通过高温热解混合金属MOFs制备结构完整、边界清晰的石墨化碳纳米棒也是一个挑战

Benefits of technology

[0011]本发明至少具有以下有益效果:本发明的ZnFe-BMOFs纳米棒在高温惰性的气氛中热解,由于ZnFe-BMOFs纳米棒中Zn2+的存在,降低了ZnFe-BMOFs中Fe3+的含量,使其热解产物能够继续保持纳米棒的结构,所得热解产物中包含Fe和Fe3C纳米颗粒,进一步经过酸处理刻蚀去除Fe和Fe3C纳米颗粒,最终得到氮掺杂多孔碳纳米棒。具体来说,本发明具有如下优点:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117756098B_ABST
    Figure CN117756098B_ABST
Patent Text Reader

Abstract

The application relates to a nitrogen-doped porous carbon nanorod and a preparation method and application thereof, the preparation method of the nitrogen-doped porous carbon nanorod comprises the following steps: S1, pyrolyzing one-dimensional ZnFe-BMOFs nanorods under an inert atmosphere; S2, immersing the material treated in the step S1 in an excess of an acidic solution, performing solid-liquid separation after reacting for a predetermined time, and obtaining the nitrogen-doped porous carbon nanorod after washing and drying. The nitrogen-doped porous carbon nanorod prepared by the application has the advantages of high graphitization degree, large specific surface area and good dispersity, the one-dimensional structure has the advantages of fast axial electron transmission and short ion diffusion path, and the nitrogen-doped porous carbon nanorod has a wide application prospect in the field of electrochemistry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of porous carbon material preparation technology, specifically to a nitrogen-doped porous carbon nanorod, its preparation method, and its application. Background Technology

[0002] Graphitized carbon materials possess excellent electrical conductivity, which can enhance the activity and stability of methanol electro-oxidation. One-dimensional carbon materials, in particular, offer advantages such as rapid axial electron transport and short ion diffusion paths, making them even more advantageous as carrier materials for electrocatalysts. High-temperature pyrolysis of metal-organic frameworks (MOFs) is an innovative method for preparing porous carbon, but only a few reports exist on the preparation of carbon nanorods using this method (e.g., CN108976818A). Graphitized carbon materials can be prepared by pyrolyzing single-metal Fe-MOF nanorods in a high-temperature inert gas environment, but the pyrolysis products often fail to maintain a rod-like structure. Therefore, preparing structurally complete and clearly defined graphitized carbon nanorods through high-temperature pyrolysis of Fe-MOFs remains a challenge.

[0003] Mixed metal MOFs contain two or more metal ions in their structural units, and their preparation methods include direct synthesis and post-synthetic exchange. Direct synthesis involves mixing different metal precursors in a reaction solution in a specific ratio and synthesizing them in one step; this method has fewer steps and is simpler to operate. Post-synthetic exchange involves pre-preparing single-metal MOFs and then performing cation exchange; this method typically takes several days to several weeks to complete. Therefore, direct synthesis is more efficient for preparing mixed metal MOFs. However, preparing structurally complete and clearly defined graphitized carbon nanorods from mixed metal MOFs through high-temperature pyrolysis remains a challenge. Summary of the Invention

[0004] In view of the problems existing in the prior art, the purpose of this invention is to provide a method and application for preparing one-dimensional graphitized carbon materials with complete structure and clear boundaries by high-temperature pyrolysis of MOFs. The resulting nitrogen-doped porous carbon nanorods have a high degree of graphitization, large specific surface area, good dispersibility, fast axial electron transport and short ion diffusion path, and have broad application prospects in the field of electrochemistry.

[0005] The present invention adopts the following technical solution:

[0006] In a first aspect, the present invention provides a nitrogen-doped porous carbon nanorod, which is prepared from one-dimensional ZnFe-BMOF nanorods by a high-temperature pyrolysis and acid treatment process.

[0007] In a second aspect, the present invention provides a method for preparing the nitrogen-doped porous carbon nanorods described in the first aspect, comprising the following steps:

[0008] S1. One-dimensional ZnFe-BMOF nanorods were pyrolyzed at high temperature under an inert atmosphere;

[0009] S2. The material treated in step S1 is immersed in an excess of acidic solution. After a predetermined reaction time, solid-liquid separation is performed, and the material is washed and dried to obtain the nitrogen-doped porous carbon nanorods.

[0010] Thirdly, the present invention provides an application of the nitrogen-doped porous carbon nanorods described in the first aspect, wherein the nitrogen-doped porous carbon nanorods are applied in electrochemical fields including methanol electro-oxidation, water electrolysis, oxygen reduction reaction, and supercapacitors.

[0011] The present invention has at least the following beneficial effects: the ZnFe-BMOF nanorods of the present invention undergo pyrolysis in a high-temperature inert atmosphere, due to the Zn content in the ZnFe-BMOF nanorods... 2+ The presence of Fe in ZnFe-BMOFs reduces 3+ The content of [specific element] allows the pyrolysis products to retain the nanorod structure. The resulting pyrolysis products contain Fe and Fe3C nanoparticles. Further acid treatment and etching remove the Fe and Fe3C nanoparticles, ultimately yielding nitrogen-doped porous carbon nanorods. Specifically, this invention has the following advantages:

[0012] (1) In this invention, nitrogen-doped porous carbon nanorods with complete structure and clear boundaries were prepared by high-temperature pyrolysis of ZnFe-BMOFs nanorods.

[0013] (2) The nitrogen-doped porous carbon nanorods provided by the present invention have a high degree of graphitization, a large specific surface area, good dispersibility, fast axial electron transport and short ion diffusion path. Among them, the high degree of graphitization gives it excellent conductivity, the large specific surface area and good dispersibility can improve the dispersion of the loaded metal particles, and the fast axial electron transport and short ion diffusion path of the one-dimensional structure can accelerate the rate of charge transfer and mass transfer in the catalytic reaction.

[0014] (3) The nitrogen-doped porous carbon nanorods provided by the present invention, as a support for loading Pt particles, have high catalytic activity and stability when applied to methanol electro-oxidation. Attached Figure Description

[0015] Figure 1a and Figure 1b The images are scanning electron microscope (SEM) images of the ZnFe-BMOF nanorods and their pyrolysis products prepared in Example 1 of this invention.

[0016] Figure 1c X-ray diffraction pattern of the pyrolysis product prepared in Example 1 of this invention;

[0017] Figure 2a and Figure 2bThe images shown are transmission electron microscope (TEM) images and X-ray diffraction (XRD) images of the nitrogen-doped porous carbon nanorods prepared in Example 1 of this invention.

[0018] Figure 3 N1s X-ray photoelectron spectroscopy of nitrogen-doped porous carbon nanorods prepared in Example 1 of this invention;

[0019] Figure 4 Cyclic voltammetry curves of Pt / NC catalyst prepared using nitrogen-doped porous carbon nanorods as a support and commercial JM-Pt / C catalyst applied to methanol electro-oxidation activity testing.

[0020] Figure 5 This is a bar chart showing the decrease in peak forward scan current as a function of scan cycles in a N2-saturated 0.1M HClO4 + 1.0M CH3OH mixed solution of Pt / NC catalyst and JM-Pt / C catalyst as a function of the number of scan cycles, as measured by cyclic voltammetry in Example 1 of the present invention.

[0021] Figure 6 This is a transmission electron microscope image of nitrogen-doped porous carbon nanorods in Example 2 of the present invention;

[0022] Figure 7 This is a transmission electron microscope (TEM) image of the nitrogen-doped porous carbon nanorods in Example 3 of the present invention. Detailed Implementation

[0023] The embodiments of the present invention will be described in detail below. It should be emphasized that the following description is merely exemplary and not intended to limit the scope and application of the present invention. Unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other.

[0024] In this article, "room temperature" refers to 15-35℃.

[0025] In a specific embodiment of the present invention, a nitrogen-doped porous carbon nanorod is provided, which is prepared by one-dimensional ZnFe-BMOFs (ZnFe-BMOFs refers to metal-organic framework materials with Fe and Zn bimetallic coordination and 2-aminoterephthalic acid as organic ligand) nanorods through high-temperature pyrolysis and acid treatment processes.

[0026] Nitrogen-doped porous carbon nanorods prepared by high-temperature pyrolysis and acid treatment processes can maintain a one-dimensional rod-shaped structure, and have a high degree of graphitization, large specific surface area, good dispersibility, fast axial electron transport and short ion diffusion path, which have broad application prospects in the field of electrochemistry.

[0027] In a specific embodiment of the present invention, a method for preparing the nitrogen-doped porous carbon nanorods described above is also provided, which includes the following steps:

[0028] S1. One-dimensional ZnFe-BMOFs nanorods are pyrolyzed at high temperature under an inert atmosphere to remove Zn from the material. The resulting pyrolysis products contain Fe and Fe3C nanoparticles.

[0029] S2. The material treated in step S1 is immersed in an excess of acidic solution. After a predetermined reaction time, solid-liquid separation is performed. After washing and drying, the nitrogen-doped porous carbon nanorods are obtained. In step S2, the acid treatment etching removes Fe and Fe3C nanoparticles, and finally the nitrogen-doped porous carbon nanorods are obtained.

[0030] In the above preparation method, ZnFe-BMOF nanorods are pyrolyzed in a high-temperature inert atmosphere to remove Zn. Since Zn in the ZnFe-BMOF nanorods is removed... 2+ The presence of Fe in ZnFe-BMOFs reduces 3+ The content of Fe was reduced to a certain level, which solved the problem of excessive Fe agglomerates destroying the structure of pyrolysis products, allowing the pyrolysis products to maintain the structure of nanorods. Then, nitrogen-doped porous carbon nanorods were prepared by acid treatment.

[0031] In a preferred embodiment, the inert atmosphere mentioned in step S1 is at least one of nitrogen and argon; the temperature of the high-temperature pyrolysis in step S1 is above 800°C, preferably below 1200°C, for example, it can be 800°C, 850°C, 900°C, etc., and any point value within the above temperature range.

[0032] In a preferred embodiment, the acidic solution in step S2 is at least one of hydrochloric acid, nitric acid, sulfuric acid, perchloric acid, hydrofluoric acid, and acetic acid; and the reaction time in step S2 is more than 24 hours.

[0033] In a preferred embodiment, the preparation method further includes:

[0034] S0, Fe at a predetermined molar ratio 3+ Metal salts and Zn 2+ A metal salt and a predetermined amount of nitrogen source are dissolved in an N,N-dimethylformamide solution and kept at a constant temperature for a predetermined time in a reaction vessel to obtain one-dimensional ZnFe-BMOF nanorods; wherein the nitrogen source is 2-aminoterephthalic acid, or the nitrogen source is a mixture of 2-aminoterephthalic acid and terephthalic acid in a predetermined molar ratio.

[0035] In a preferred embodiment, the Fe mentioned in step S0 3+ The metal salt is at least one of ferric chloride, ferric nitrate, and ferric sulfate; the Zn mentioned in step S0 2+ The metal salt is at least one of zinc chloride, zinc nitrate, and zinc sulfate.

[0036] In the synthesis of ZnFe-BMOFs, the Fe content in the reaction solution was changed. 3+ / Zn 2+ The morphology of ZnFe-BMOFs can be adjusted by changing the molar ratio of 2-aminoterephthalic acid / terephthalic acid.

[0037] In a preferred embodiment, Fe in step S0 3+ Metal salts and Zn 2+ In metal salts, Fe 3+ / Zn 2+ The molar ratio of Zn is 1 / 16-1, that is, Zn 2+ The molar amount of Fe is 3+ The molar amount can be 1-16 times, for example, 1 / 16, 1 / 8, 1 / 4, 1 / 2, 2 / 3, 3 / 4, or 1, or any point value within the above molar ratio range. This is achieved by controlling the Fe content in the metal salt. 3+ / Zn 2+ The molar ratio is 1 / 16-1, which ensures that the obtained ZnFe-BMOFs have a rod-like structure.

[0038] In a preferred embodiment, when the nitrogen source in step S0 is a mixture of 2-aminoterephthalic acid and terephthalic acid with a predetermined molar ratio, the molar ratio of 2-aminoterephthalic acid to terephthalic acid is 1 / 4-4, that is, the molar amount of 2-aminoterephthalic acid is 0.25-4 times the molar amount of terephthalic acid. For example, it can be 1 / 4, 1 / 2, 1, 3 / 2, 2, 5 / 2, 3, 7 / 2 or 4, and any point value within the above molar ratio range. Terephthalic acid can adjust the N element content in ZnFe-BMOFs.

[0039] In a preferred embodiment, the temperature of the reactor in step S0 is 80-250°C, for example, it can be 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C or 250°C, or any point value within the above temperature range; the reaction time is 20 hours or more.

[0040] The present invention also provides an application of the nitrogen-doped porous carbon nanorods, which are used as carrier materials in electrochemical fields including methanol electro-oxidation, water electrolysis, oxygen reduction reaction, and supercapacitors.

[0041] Preferably, the nitrogen-doped porous carbon nanorods, when used as a support material to load Pt particles, exhibit high catalytic activity and stability when applied to the electro-oxidation of methanol.

[0042] The present invention will be further illustrated by more specific embodiments below, wherein the room temperature in the following embodiments is 25°C.

[0043] Example 1

[0044] Nitrogen-doped porous carbon nanorods were prepared using the following method:

[0045] (1) 1.24 mmol of ferric chloride, 4.96 mmol of zinc nitrate and 2.48 mmol of 2-aminoterephthalic acid were dissolved in 40 mL of N,N-dimethylformamide. The mixture was heated to 110 °C in a reaction vessel, kept at that temperature for 20 h, cooled to room temperature, washed and dried to prepare ZnFe-BMOF nanorods;

[0046] (2) Place the material obtained in step (1) in a quartz boat in a quartz tube furnace, heat it to 900°C in nitrogen, keep it at that temperature for 2 hours, and then let it cool naturally to room temperature.

[0047] (3) Disperse 200 mg of the material obtained in step (2) in an excess of 200 mL of 0.5 M nitric acid aqueous solution, stir at room temperature for 24 h, and then wash and dry.

[0048] The ZnFe-BMOF nanorods prepared in step (1) of this embodiment were examined using a scanning electron microscope (Hitachi SU8010). Figure 1a ) and the pyrolysis products of step (2) Figure 1b Characterize it. Figure 1c The X-ray diffraction pattern of the pyrolysis product in step (2) shows that the pyrolysis product contains Fe and Fe3C particles.

[0049] It is evident that the pyrolysis products of ZnFe-BMOF nanorods can maintain their original morphological characteristics and dispersion state. For example... Figure 2a As shown, nitrogen-doped porous carbon nanorods obtained by acid treatment of the pyrolysis products of ZnFe-BMOFs nanorods were characterized using transmission electron microscopy (FEI Tecnai G2 F30). It was observed that the metal particles within the pyrolysis products of ZnFe-BMOFs nanorods were etched away by the acid treatment. Figure 2b On the XRD curve, the diffraction peaks at 26.4° and 42.8° belong to the (002) and (100) crystal planes of graphitized carbon, and their sharp diffraction peaks indicate that it has a high degree of graphitization. Its specific surface area, measured by the BET method, is 733.3 m². 2 / g is twice that before etching. For example... Figure 3 As shown, X-ray photoelectron spectroscopy characterization revealed that nitrogen in nitrogen-doped porous carbon nanorods exists mainly in graphitic and pyridine forms.

[0050] 100 mg of the porous nitrogen-doped carbon nanorods prepared in this example were ultrasonically dispersed in 50 mL of deionized water. 6.2 mL of an aqueous solution of 38.6 mM chloroplatinic acid hexahydrate was added. After stirring at room temperature for 1 h, 50 mL of an aqueous solution containing 400 mg of sodium borohydride was added. After stirring for another 2 h, the mixture was filtered and washed with deionized water and placed in a vacuum drying oven at room temperature overnight to prepare the Pt / NC catalyst.

[0051] A glassy carbon electrode, an Ag / AgCl electrode, and a Pt wire were used as the working electrode, reference electrode, and counter electrode, respectively. Electrochemical performance was tested using a Model RST 5200 electrochemical workstation from Zhengzhou Shiruisi Instrument Technology Co., Ltd. The activity of methanol electro-oxidation was measured in a nitrogen-saturated mixed solution of 0.1M perchloric acid and 1.0M methanol at room temperature, with a scan potential range of 0–1.0 V and a scan rate of 50 mV / s. Figure 4 As shown, the Pt / NC catalyst prepared using nitrogen-doped porous carbon nanorods as a support exhibits a methanol electro-oxidation specific activity of 841.6 mA / mgPt, which is 1.7 times that of the commercial JM-Pt / C catalyst.

[0052] Figure 5 This is a bar chart showing the decrease in peak forward scan current as a function of scan cycles for Pt / NC catalyst and JM-Pt / C catalyst in a N2-saturated 0.1M HClO4 + 1.0M CH3OH mixed solution at room temperature, measured by cyclic voltammetry in Example 1 of this invention. Figure 5 It is evident that the Pt / NC catalyst of the present invention exhibits better stability.

[0053] Example 2

[0054] Nitrogen-doped porous carbon nanorods were prepared using the following method:

[0055] (1) 2.48 mmol of ferric sulfate, 4.96 mmol of zinc chloride, 1.66 mmol of 2-aminoterephthalic acid and 0.83 mmol of terephthalic acid were dissolved in 40 mL of N,N-dimethylformamide; the mixture was heated to 110 °C in a reaction vessel, kept at that temperature for 20 h, cooled to room temperature, washed and dried to prepare ZnFe-BMOF nanorods;

[0056] (2) Place the material obtained in step (1) in a quartz boat in a quartz tube furnace, heat it to 800°C in argon, keep it at that temperature for 2 hours, and then let it cool naturally to room temperature.

[0057] (3) 200 mg of the material obtained in step (2) was ultrasonically dispersed in 200 mL of 0.5 M perchloric acid aqueous solution, stirred at room temperature for 24 h, washed and dried.

[0058] like Figure 6As shown, the porous nitrogen-doped carbon nanorods prepared in this embodiment were characterized by transmission electron microscopy. The results show that the porous nitrogen-doped carbon nanorods obtained in this embodiment have a uniform structure and good dispersion.

[0059] Example 3

[0060] (1) 2.48 mmol of ferric chloride, 4.96 mmol of zinc nitrate, 0.83 mmol of 2-aminoterephthalic acid and 1.66 mmol of terephthalic acid were dissolved in 40 mL of N,N-dimethylformamide; the mixture was heated to 110 °C in a reaction vessel, kept at that temperature for 20 h, cooled to room temperature, washed and dried to prepare ZnFe-BMOF nanorods;

[0061] (2) Place the material obtained in step (1) in a quartz boat in a quartz tube furnace, heat it to 1000°C in nitrogen, keep it at that temperature for 2 hours, and then let it cool naturally to room temperature.

[0062] (3) Disperse 200 mg of the material obtained in step (2) in 200 mL of 0.5 M hydrochloric acid aqueous solution, stir at room temperature for 24 h, wash and dry.

[0063] like Figure 7 As shown, the porous nitrogen-doped carbon nanorods prepared in this embodiment were characterized by transmission electron microscopy. The results show that the porous nitrogen-doped carbon nanorods obtained in this embodiment have a uniform structure and good dispersion.

[0064] The above description provides a further detailed explanation of the present invention in conjunction with specific / preferred embodiments, and it should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various substitutions or modifications can be made to these described embodiments without departing from the concept of the present invention, and all such substitutions or modifications should be considered within the scope of protection of the present invention. In the description of this specification, the reference to terms such as "an embodiment," "some embodiments," "preferred embodiment," "example," "specific example," or "some examples," etc., indicates that the specific features, structures, materials, or characteristics described in connection with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any suitable manner in one or more embodiments or examples. Without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions, and modifications can be made herein without departing from the scope of protection of the patent application.

Claims

1. A nitrogen-doped porous carbon nanorod, characterized in that, One-dimensional ZnFe-BMOF nanorods were prepared by high-temperature pyrolysis and acid treatment in an inert atmosphere; wherein the nitrogen source used for the ZnFe-BMOF nanorods was 2-aminoterephthalic acid, or a mixture of 2-aminoterephthalic acid and terephthalic acid, and the molar ratio of 2-aminoterephthalic acid / terephthalic acid was 1 / 4-4; the Fe content in the ZnFe-BMOF nanorods was... 3+ / Zn 2+ The molar ratio is 1 / 16-1.

2. A method for preparing nitrogen-doped porous carbon nanorods according to claim 1, characterized in that, Includes the following steps: S0, according to Fe 3+ / Zn 2+ The molar ratio is 1 / 16-1, and Fe... 3+ Metal salts and Zn 2+ Metal salts and a predetermined amount of nitrogen source are dissolved in N,N-dimethylformamide solution and kept at a constant temperature for a predetermined time in a reaction vessel to obtain one-dimensional ZnFe-BMOF nanorods. The nitrogen source is 2-aminoterephthalic acid, or a mixture of 2-aminoterephthalic acid and terephthalic acid, and the molar ratio of 2-aminoterephthalic acid to terephthalic acid is 1 / 4-4. S1. One-dimensional ZnFe-BMOFs nanorods are pyrolyzed at high temperature under an inert atmosphere to remove Zn and obtain pyrolysis products that retain the structure of the nanorods. S2. The material treated in step S1 is immersed in an excess of acidic solution and reacted for a predetermined time to remove the Fe and Fe3C nanoparticles contained in the pyrolysis products. After solid-liquid separation, the material is washed and dried to obtain the nitrogen-doped porous carbon nanorods.

3. The preparation method according to claim 2, characterized in that, The inert atmosphere mentioned in step S1 is at least one of nitrogen and argon; the high-temperature pyrolysis temperature mentioned in step S1 is above 800 °C.

4. The preparation method according to claim 2, characterized in that, The acidic solution mentioned in step S2 is at least one of hydrochloric acid, nitric acid, sulfuric acid, perchloric acid, hydrofluoric acid, and acetic acid; the reaction time in step S2 is more than 24 hours.

5. The preparation method according to claim 3, characterized in that, The temperature of the high-temperature pyrolysis in step S1 is below 1200 °C.

6. The preparation method according to claim 5, characterized in that, Fe described in step S0 3+ The metal salt is at least one of ferric chloride, ferric nitrate, and ferric sulfate; the Zn mentioned in step S0 2+ The metal salt is at least one of zinc chloride, zinc nitrate, and zinc sulfate.

7. The preparation method according to claim 5, characterized in that, The temperature of the reactor in step S0 is 80-250 °C; the reaction time is more than 20 h.

8. An application of the nitrogen-doped porous carbon nanorods according to claim 1, characterized in that, The nitrogen-doped porous carbon nanorods are used in electrochemical fields including methanol electro-oxidation, water electrolysis, oxygen reduction reaction, and supercapacitors.

Citation Information

Patent Citations

  • Porous ordered carbon rob based cellulose composite material as well as preparation method and application thereof

    CN108976818A

  • Preparation method of size-controllable microporous carbon nanorod

    CN106829918A